2020
DOI: 10.1093/toxres/tfaa051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dimethoate toxicity on fertilization and on embryonic development of Paracentrotus lividus (Lamarck, 1816)

Abstract: Organophosphates are a large class of chemicals with anticholinesterase action insecticides. Dimethoate belongs to the class of organophosphates and it is used for agriculture purpose. Its main toxicological role in animals and humans is the inhibition of the activity of acetylcholinesterase. Although it is not considered genotoxic, carcinogenic and teratogen, there is evidence of increased pup mortality in developmental neurotoxicity studies. Since there is scant published literature about developmental toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Randomly, the application for all these insecticides are used for mosquito control [ 217 ], control a variety of insects that attack fruits, vegetables, landscaping plants and shrubs and also act as acarida [ 218 , 219 ]. It also can be used on pets to control ticks and insects, such as fleas and ants [ 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 ].…”
Section: Various Classes Of Insecticides Detection By Optical Sensorsmentioning
confidence: 99%
“…Randomly, the application for all these insecticides are used for mosquito control [ 217 ], control a variety of insects that attack fruits, vegetables, landscaping plants and shrubs and also act as acarida [ 218 , 219 ]. It also can be used on pets to control ticks and insects, such as fleas and ants [ 220 , 221 , 222 , 223 , 224 , 225 , 226 , 227 , 228 ].…”
Section: Various Classes Of Insecticides Detection By Optical Sensorsmentioning
confidence: 99%
“…However, many studies have shown adverse effects on mammalian [6][7][8] . Several studies have documented that the carcinogenicity [9] and developmental toxicity [10,11] of dimethoate which can lead to a reduction in plasma cholinesterase [12] . Likewise, BaP has been characterized as a stronger carcinogen than other PAHs compounds [13] which can cause DNA damage and plays a role in lung carcinogenesis [14], atherosclerosis [15] and so on [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic fauna exposed to dimethoate exhibited muscular tetany, loss of buoyancy ( Heteropneustes fossilis , cat fish: Pandey et al, 2009; Srivastava et al, 2010). , erratic swimming, decreased rate of opercular movement, copious mucus secretion, reduced agility, loss of balance (common carp, Cyprinus carpio : Singh et al, 2009), DNA damage, LPO and ROS stress in brain and liver tissues (Rainbow trout, Oncorhynchus mykiss : Dogan et al, 2011), developmental defects, and so forth (sea urchins Paracentrotus lividus : Scalisi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%